A30 FIRST YEAR OUTCOMES FROM A PROVINCIALLY FUNDED NON-FIBROSIS RESTRICTED HEPATITIS C TREATMENT PROGRAM IN PRINCE EDWARD ISLAND. (1st March 2018) - Francheville, J W; Rankin, R; Beck, J N; Hoare, C; Khan, R; Materniak, S; German, G; Barrett, L; Wall, N Bunimov; Smyth, D
Abstract: Background: The availability of novel curative therapies for hepatitis C virus (HCV) infection has created a unique opportunity to mitigate complications of untreated disease, and improve both clinical programming and treatment access. Between September 2014 and October 2015 local care providers, government, industry, and HCV community groups in Prince Edward Island (PEI) created a province-wide model of care. Core components of the program include: centralized referral, triage, and intake by HCV nurse specialist; HCV treatment specialists; non-fibrosis restricted public access to direct-acting antiviral (DAA) therapy; patient education, follow-up with public and industry-affiliated nursing support; and voluntary patient enrollment into a treatment registry. Aims: We evaluated performance of this care model, and both demographic, outcome, and treatment-effectiveness measures for treated patients. Methods: Using a prospective observational study design, all chronic HCV referrals received from April 2015 to April 2016 were recorded in the program database. Primary analysis examined program parameters including the time from referral to assessment/treatment, as well as the number of referrals, assessments and treatment initiations. A secondary analysis involved evaluation of treatment effectiveness among all treated patients using intent-to-treat analysis. Results: In the first year of the program, 242 patient referrals were received, 123 patients were seen for intake assessments and 93 initiated on DAAs with prioritization to patients with advanced fibrosis. This is compared to only 4 treatment initiations in the province in the 2 years prior to program implementation. The median time from assessment to treatment initiation was 3 weeks. Overall, 82 of the 84 (97.6%) patients for whom outcome data was available achieved sustained virologic response (SVR) at post-treatment week 12; 1 was lost to follow-up and 1 died following therapy completion from an unrelated event. Detailed demographics and on-treatment data was obtained from 70 patients enrolled in the voluntary treatment registry of whom 27.1% were cirrhotic, 24.3% treatment-experienced, and 82.4% reported on-treatment adverse events. No adverse events were deemed serious or resulted in treatment discontinuation. Conclusions: Initial data from the PEI program demonstrates how comprehensive care programs can be used to facilitate timely access to assessment and initiation of HCV therapy. High SVR rates seen in our real-world cohort were reflective of that seen in registration trials including in difficult to treat patient populations. It is hoped that similar models of care throughout Canada will facilitate broader access to curative HCV therapies, especially in under resourced settings. Funding Agencies: Health Research Foundation of Innovative Medicines Canada, Dalhousie Medical Research Foundation